(untitled) (International journal of artificial intelligence, 2025)
This article analyzes the theoretical foundations of the shadow economy, the factors influencing its formation, and its socio-economic consequences. Comparative experiences of Uzbekistan and foreign countries are examined, and recommendations for reducing the shadow economy are proposed.